The Effect of the Covering with Black Cloth and Ethanol Concentration on the Curcuminoid Contents and Antioksidant Activity of Temulawak (Curcuma xanthorrhiza) Chip Extracts - Sri Anggrahini; Raden Rara Safitriani; Umar Santosa (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2007)
The aim of this research was to find out the curcuminoid content and antioxidant activity of temulawak (Curcuma xanthorriza) chip extracts under specific treatment. This research was started with preparation of temulawak chips. Which were made from 2 treatment of sun drying, those which were convered with black cloth and those without cover. The quantity of three types of know curcuminoids of temulawak chips were analyzed by HPCL after axtraction with 0%, 5% and 95% etanol solvent. Antioxidant activities in the extracts were measured by ferri thiocyanate and thiobarbituric acid methods. The result indicated that drying with black cloth cover showed higher curcuminoid content and antioxidant activity compared with those without black cloth cover, but drying with black cloth cover had no effect on the type of curcuminoids. The antioxidant activity of temulawak chip was highest with the type of curcuminoids being bisdemetoxicurcumine, demetoxicurcumine and curcumine when the temulawak chips were extracted with 95% ethanol. While the type of curcuminoids were only demetoxicurcumine and curcumine, when temulawak chips were extracted with 0% and 50% ethanol. Key words : Temulawak chips, curcuminoid, ethanol, antioxidant activity.